Cross-Sectional Study Protocol for the COVID-19 Impact Survey of Mothers and Their 7–11 Year Old Children in Alberta, Canada - Letourneau, Nicole; McDonald, Sheila; MacKay, Lyndsay Jerusha; Bell, Rhonda C.; Hetherington, Erin; Deane, Andrea J.; Dewey, Deborah; Edwards, Sarah; Field, Catherine J.; Giesbrecht, Gerald F.; Graham, Susan; Lebel, Catherine; et al. (Frontiers in Psychiatry, 2021)
Objectives: Our aim is to understand the effect of the COVID-19 pandemic on families who have been followed longitudinally in two cohorts studied in Alberta, Canada. We will examine household infections during the COVID-19 pandemic, financial impact, domestic violence, substance use, maternal mental health and well-being, child school and daily life, and relationships in the home. We will identify risk and protective factors of these outcomes using longitudinal data that can inform policy and government resource allocation in future disasters. Methods: Mothers who are currently participating in two longitudinal studies, Alberta Pregnancy Outcomes and Nutrition (APrON; N=1800) and All Our Families (AOF: N=2534) were eligible to participate. Mothers were invited to complete the baseline COVID-19 Impact Survey (20-30 minutes) within 4 months of March 15, 2020, which was when the province of Alberta, Canada, implemented school closures and physical-distancing measures to prevent the spread of COVID-19. Mothers were asked to report on their own, their child’s and their family’s functioning. Mothers were re-surveyed at 6 months after completion of the initial COVID-19 Impact Survey, and will be re-surveyed again at 12 months. Results: Responses from participants in both cohorts will be examined in harmonized analyses as well as separately. Descriptive, multivariable analysis will be undertaken to examine risk and resiliency over time and factors that predict mental health and well-being. Conclusions: This study will provide timely information on the impact of COVID-19 for Albertan families. It will identify risk and protective factors for mental health and well-being among contemporary urban families supported by a publicly funded health care system to inform allocation of resources to support those most vulnerable during a global pandemic.